PENERAPAN STRATEGI PEMBELAJARAN AKTIF BEACH BALL UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KELARUTAN DI KELASXI MIPA 6 SMA NEGERI 5 PEKANBARU - Fharadilla, Anita; Erviyenni, Erviyenni; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this research was to improve the student activity and achievement used Beach Ball learning strategy on solubility equilibrium subject at XI MIPA 6 of Senior High School (SMAN) 5 Pekanbaru in academic year 2017/2018. This research was an action research with two cycle design. Each cycleconsisted of two meetings included four stages of implementation: planning, action, observation, and reflection. The collecting data used observation and test. The analysis data was describ with descriptively. The result of action showed that learning activity percentage of student improved and reached the success criteria. The learning activityof student percentage in first cycle was 57,24% with enough category and the secondcycle was 68,70% with good category. Student achievement was seen from mastery learning that enhances and have achieved success criteria. The percentage of student achievement in the first cycle was 79,70% and the second cycle was 89,74%. Based on the results obtained, it can be concluded that using IDEAL problem solving strategy can improve the activity and student achievement.Keyword: Beach Ball learning strategy, student learning activity, student achievement